Airway obstruction and the risk of myocardial infarction and death from coronary heart disease: a national health examination survey with a 33-year follow-up period - Mattila Tiina; Vasankari Tuula; Rissanen Harri; Knekt Paul; Puukka Pauli; Heliövaara Markku (Springer Netherlands, 2022)
Chronic obstructive pulmonary disease (COPD) has been associated with coronary mortality. Yet, data about the association between COPD and acute myocardial infarction (MI) remain scarce. We aimed to study airway obstruction as a predictor of MI and coronary mortality among 5576 Finnish adults who participated in a national health examination survey between 1978 and 1980. Subjects underwent spirometry, had all necessary data, showed no indications of cardiovascular disease at baseline, and were followed up through record linkage with national registers through 2011. The primary outcome consisted of a major coronary event—that is, hospitalization for MI or coronary death, whichever occurred first. We specified obstruction using the lower limit of normal categorization. Through multivariate analysis adjusted for potential confounding factors for coronary heart disease, hazard ratios (HRs) (with the 95% confidence intervals in parentheses) of a major coronary event, MI, and coronary death reached 1.06 (0.79–1.42), 0.84 (0.54–1.31), and 1.40 (1.04–1.88), respectively, in those with obstruction compared to others. However, in women aged 30–49 obstruction appeared to predict a major coronary event, where the adjusted HR reached 4.21 (1.73–10.28). In conclusion, obstruction appears to predict a major coronary event in younger women only, whereas obstruction closely associates with the risk of coronary death independent of sex and age.